2017
DOI: 10.1108/jkm-10-2016-0439
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of guanxi and face on the relationship between psychological motivation and knowledge-sharing in China

Abstract: Purpose This study aims to investigate how psychological motivations influence the knowledge-sharing intention of employees and how these effects are moderated by traditional Chinese culture. Design/methodology/approach A questionnaire survey was conducted in China to test the research model. The target samples comprised MBA students who have enough practical experience, as well as considerable academic experience. Findings The results suggest that anticipated reciprocal relationships, anticipated extrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 63 publications
3
54
0
2
Order By: Relevance
“…The sense of self-worth is a purely self-motivational factor and can be also regarded as an intrinsic motivation. When knowledge contributors find that their offerings are beneficial to others and are positively evaluated, their confidence and sense of self-achievement will be increased, which in turn can also facilitate their participation in knowledge sharing [1,12,16,20]. Generally, doctors usually regard their missions as helping more patients, so they are more likely to engage in eHealth.…”
Section: Anticipated Outcomesmentioning
confidence: 99%
“…The sense of self-worth is a purely self-motivational factor and can be also regarded as an intrinsic motivation. When knowledge contributors find that their offerings are beneficial to others and are positively evaluated, their confidence and sense of self-achievement will be increased, which in turn can also facilitate their participation in knowledge sharing [1,12,16,20]. Generally, doctors usually regard their missions as helping more patients, so they are more likely to engage in eHealth.…”
Section: Anticipated Outcomesmentioning
confidence: 99%
“…Knowledge is an essential resource for all businesses of the globalization era (Ding et al, 2017;Nonaka & Toyama, 2015;Razak et al, 2016). As a critical asset, knowledge is the key driver that has been constantly sought, maintained, and developed by many industries including the banking industry (Olapegba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The factors behind knowledge-sharing behavior have been extensively investigated with different designs and contexts by scientists worldwide, such as in the United States, United Kingdom, Europe, Africa, and Asia (Caniels et al, 2017;Ding et al, 2017;Fullwood & Rowley, 2017;Mafabi et al, 2017;Mahyarni et al, 2012;Wang & Noe, 2010). Scholars have predicted that this direction of studies only continues to grow in popularity over the next two decades (Tea & Sun, 2012;Ding et al, 2017;Fullwood & Rowley, 2017;Mafabi et al, 2017). This prediction proves the increasing attention of scholars on knowledge-sharing research in the world today.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Chinese people are found to be hesitant to share valuable information to other employees who are considered not as part of the "in-group" members, as revealed for example in a comparison between manager views in Australian and Taiwanese-owned firms (Chow et al, 1999). Due to their seemingly low trust towards outsiders and a fear of potential loss of individual gains (Ding et al, 2016), it is seen as inconceivable for the Chinese to devote considerable time for converting privately held tacit knowledge into public domains that can be accessible by everyone in organizations. The same would be expected in Brazil, however, a comparative study on knowledge sharing in plants in Brazil, China and Russia, found that Brazilian employees are the most enthusiastic about sharing information with others in their organization (Ardichvili et al, 2006).…”
Section: Cultural Barriers To Knowledge Sharing In China and Brazilmentioning
confidence: 99%
“…Third, the role of face, or mianzi, and the importance of face-saving for Chinese (Buckley et al, 2006;Ding et al, 2016) exert some emotional pressures on the knowledge seekers, thus implicating their social interactions with the knowledge contributors. Especially for those with higher hierarchical position, fear of losing their social standing and authority in front of their peers or subordinates might undermine their willingness to raise request for knowledge sharing (McAdam et al, 2012).…”
Section: Cultural Barriers To Knowledge Sharing In China and Brazilmentioning
confidence: 99%